The analysis of the effect of cutting mode and coolant on formation of burrs when drilling aluminum alloy - A.G. Kisel; D. S. Makashin; D. Yu. Belan; K. V. Averkov (Омский научный вестник)
Drilling is an extremely important process widely used in the manufacture of fuel control equipment. The sustainable drilling process of aluminum alloy is promising for today's industry, which reduces energy and coolant consumption without compromising the quality of workmanship. This article examines the effect of feed and spindle speed on maximum power input, the height of the burrs generated during drilling, and the resulting deviation in the diameter of the drilled hole.